Propuesta de un modelo administrativo basado en la caracterización de las organizaciones del sector industrial de la ciudad de Loja año 2013-2014 - Jaramillo Arévalo, María del Cisne (2014)
This final paper qualification is aimed at proposing a model designed based on the theories of different authors and characterization of the administrative organizations of the industrial sector of the city of Loja. The model will allow companies to maintain a flexible dynamic structure has to contribute to improve competitiveness, administrative operations and facilitate compliance of organizations with the environment, this study also contribute to disagree whether the organizational characteristics learned in theory have been applied by industry organizations. With the analysis and description of the main administrative contributions that have been made from different fields of study as the results obtained in the characterization, it is proposed that companies maintain procedures formally written, that managers maintain a democratic leadership style, a type multidirectional communication that fit recognition, training and assignment of duties as really significant motivational factors, among other features that are part of the administrative model, as detailed in the present study.